Solid phase extraction of zinc with octadecyl silica membrane disks modified by N,N’-disalicylidene-1,2-phenylendiamine and determination by flame atomic absorption spectrometry - Shabany, M.; Shabani, Ali Mohammad Haji; Dadfarnia, Shayessteh; Gorji, Alireza; Ahmadi, Seyyed Hamid (Eclética Química, 2008)
A procedure for separation and preconcentration of trace amounts of Zn(II) from aqueous media is proposed. The procedure is based on the adsorption of Zn2+ on octadecyl bonded silica membrane disk modified with N,N’-disalicylidene-1,2-phenylendiamine at pH 7. The retained zinc ions were then stripped from the disk with a minimal amount of 1.5 mol L-1 hydrochloric acid solution as eluent, and determined by flame atomic absorption spectrometry. Maximum capacity of the membrane disk modified with 5 mg of the ligand was found to be 226 μg Zn2+. The relative standard deviation of zinc for ten replicate extraction of 10 μg zinc from 1000 mL samples was 1.2%. The limit of detection of the proposed method was 14 ng of Zn2+ per 1000 mL. The method was successfully applied to the determination of zinc in natural water samples and accuracy was examined by recovery experiments and independent analysis by graphite furnace atomic absorption spectrometry (GFAAS).